Perlindungan Hukum terhadap Hak Cipta Karya Seni Berdasarkan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Jacqueline , Jacqueline; Sudarto, Sudarto (LITERATUS, 2025)
Every human being has reason and mind that is able to create science, technology and works of art, where the creation of the work of art must be respected and appreciated as a work of creation which is an expression of the creative ability of the creator. In its development, the work of creation of a human being or a group of people who have created the work of art must be protected and have copyright for their work so that it can provide a decent life for the creator of the work of art. For a work of art, the State recognizes property rights by guaranteeing rights and providing protection for the owners or holders of exclusive rights. By ratifying Trips, Indonesia automatically recognizes and provides legal protection for someone's creative work that has a value called KI. For that, it will be further studied how the regulation of artistic copyright is based on Law Number 28 of 2014 concerning copyright and how the legal protection of artistic copyright is based on Law Number 28 of 2014 concerning copyright. The research method used in this study is the normative legal research method. From the results of the study, it was found that the Regulation of Artwork Copyright Based on Law Number 28 of 2014 concerning Copyright, Basically, the regulation of artistic copyright based on Law 28/2014 is regulated in Article 1 number 1, number 2 and number 3 Jo Article 38 Jo Article 40 of Law 28/2014 and Legal Protection of Artwork Copyright Based on Law Number 28 of 2014 concerning Copyright, with the existence of Law 28/2014 which fulfills the elements of protection and development of the creative economy, it is hoped that the contribution of the Copyright and Related Rights sector to the country's economy can be more optimal. A creation must prioritize originality or authenticity and real so that a creation in the fields of art, literature and science can have full copyright. From the results of the research for improvement, it is expected that new laws and regulations on copyright of works of art will be made immediately and DJKI must cooperate with the relevant ministries to protect the copyright of works of art.